2001
DOI: 10.2114/jpa.20.159
|View full text |Cite
|
Sign up to set email alerts
|

Local Temperature Changes and Human Skeletal Muscle Metabolism.

Abstract: The aim of this review is to describe the effects induced by local temperature changes on human skeletal muscle metabolism. More specifically, we will consider the influence of temperature on the mechanical properties of muscle contraction, on aerobic metabolism, anaerobic metabolism and on the Lohmann reaction. The text has been voluntarily organized on the basis of a simple bioenergetic model describing the different energy fluxes appearing in the muscle system. This approach should better highlight some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
(93 reference statements)
1
4
0
Order By: Relevance
“…This mathematical result is consistent with the fact that n(T) seems to decrease at low T (Bottinelli and Reggiani 2000). A more exhaustive discussion on the T dependence of the bioenergetic equation may be found in Binzoni and Delpy (2001).…”
Section: Oxidative Metabolism and Temperature: Near Infrared Spectrossupporting
confidence: 85%
“…This mathematical result is consistent with the fact that n(T) seems to decrease at low T (Bottinelli and Reggiani 2000). A more exhaustive discussion on the T dependence of the bioenergetic equation may be found in Binzoni and Delpy (2001).…”
Section: Oxidative Metabolism and Temperature: Near Infrared Spectrossupporting
confidence: 85%
“…For human skeletal muscle, locally reducing temperature generally reduces the ability of muscle to generate active tension 26, 27 , but little is known about how local tissue cooling affects biochemical and molecular processes in human muscle tissue 28 . One published model predicts a decrease of 0.17 mM of ATP and 0.54 mM of phosphocreatine per 1 °C reduction in IM temperature 8 , however local cooling of the quadriceps muscle group with a cuff perfused with 0 °C water for 1 hour does not change the levels of ATP, creatine or phosphocreatine 29 .…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that developing techniques of measuring local oxygen uptake was essential in order to study human muscle metabolism over a large range of Tm 60) . Recently, several studies directly measured the temperature dependence of muscle metabolism using near infrared spectroscopy (NIRS) [61][62][63] .…”
Section: Neuromuscular Functionmentioning
confidence: 99%